Prevention of dental caries in children – opportunities and limitations - Olczak-Kowalczyk, Dorota; Kowalczyk, Wojciech (Polish Journal of Public Health, 2013)
According to the results of epidemiological study – “Monitoring Zdrowia Jamy Ustnej” (Monitoring of Oral Health), Poland belongs to the countries of persistent high prevalence and intensity of caries disease. Caries lesions appear in early childhood and occur in over 50% of children of the age of 3 and in over 80% of children of 12. The analysis of basic determinants of planning prophylactic activity and strategy proposal of prevention against caries disease in children and adolescents is very important.The paper discusses etiologic factors of caries disease directly and indirectly connected with the development of the disease process. The authors point to the relationship between the occurrence of early childhood caries and colonization time of oral cavity by cariogenic germs and present the relationship between caries in deciduous and permanent teeth. The authors emphasize the necessity of early prophylactic activity already in fetal period (primary primal prophylaxis) and the importance of long-term prophylaxis. Prophylactic strategies are discussed: population and corporate strategies based on the assessment of caries risk.Attention has been paid to the advantages and disadvantages of prophylactic strategies from Public Health point of view. Epidemiologic data are presented indicating the necessity of combining prevention in population with high prophylaxis and individual risk prophylaxis carried out by dentists. The principles of individual caries prophylaxis and methods of proceeding recommended for patients with risk assessed as low, moderate and high are discusse